2023
DOI: 10.54371/jiip.v6i2.1463
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penggunaan Laboratorium Virtual Berbantukan Media PHET terhadap Keterampilan Berpikir Kreatif Siswa pada Materi Listrik Dinamis

Abstract: Memiliki strategi image yang baik adalah suatu hal yang harus dilakukan. Brand berarti gambaran positif yang melekat di masyarakat sehingga perusahaan atau lembaga selalu di ingat dalam jangka yang panjang. Sama halnya dengan perguruan tinggi di tuntut memiliki image yang positif memiliki keunggulan di banding dengan lainnya, untuk keberhasilan mutu kualitas serta lulusan yang dapat di terima bekerja di dunia pendidikan. Penelitian ini bertujuan untuk mengetahui daya saing lulusan prodi Pendidikan Guru Madrasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Mastery of concepts can also be increased by the problem-based learning model in collaboration with PhET simulations because students are faced directly with problems, so it can encourage students to learn actively and independently, build new knowledge by exchanging ideas and helping each other in completing assignments or LKPD which is accompanied by the help of virtual media PhET simulations which functions to visualize abstract concepts in optical equipment material. Not only that, utilizing the PhET virtual laboratory media can help students more easily understand the material taught by Nur Aisyah et al, (2023). The results of previous research also found that there was an influence of the use of virtual laboratory media on students' conceptual understanding Nur Hikmah (2017).…”
Section: Mastery Of Conceptsmentioning
confidence: 88%
“…Mastery of concepts can also be increased by the problem-based learning model in collaboration with PhET simulations because students are faced directly with problems, so it can encourage students to learn actively and independently, build new knowledge by exchanging ideas and helping each other in completing assignments or LKPD which is accompanied by the help of virtual media PhET simulations which functions to visualize abstract concepts in optical equipment material. Not only that, utilizing the PhET virtual laboratory media can help students more easily understand the material taught by Nur Aisyah et al, (2023). The results of previous research also found that there was an influence of the use of virtual laboratory media on students' conceptual understanding Nur Hikmah (2017).…”
Section: Mastery Of Conceptsmentioning
confidence: 88%
“…The purpose of IoT simulation is to facilitate developers, researchers, and other users in testing, developing, and validating IoT solutions without the requirement of using real physical hardware. Simulators can be utilized to offer practical experience and enhance students' abstract and critical thinking abilities without the potential hazards associated with using physical devices [25].…”
Section: Description: V1: the Block Diagram Design Of The Iot Virtual...mentioning
confidence: 99%